Pathogenic streptococci : from genomics to systems biology and control - Li, Yuqing (Of Sichuan da xue); Zhou, Xung (Caister Academic Press, 2019)
Streptococcus is a diverse genus of Gram-positive bacteria commonly found in multiple locations of their human and animal hosts e.g. the oral cavity and the upper respiratory tract. Many streptococci are commensals thus play a role in colonization resistance of the host. Others, however, are pathogenic and are responsible for a range of invasive and noninvasive diseases with high morbidity and mortality worldwide. Streptococci undergo frequent and extensive horizontal gene transfer leading to the emergence of drug resistant strains. This, combined with the current lack of effective anti-streptococcal vaccines, has led to a huge amount of research into the genomics to systems biology of these important bacteria. This timely review, edited by Yuqing Li and Xuedong Zhou, provides a comprehensive overview of the current knowledge of the most important hot-topics in streptococcal research. Topics covered include: CRISPR-Cas systems; genetic regulation by small RNAs; signal transduction by cyclic dinucleotide second messengers; the VicRK and ComDE two-component systems; mobile genetic elements; regulation of cell division; application of omics and bioinformatics tools; intrageneric and intergeneric interactions by oral streptococci; the hypervirulent M1T1 clone of GAS; Streptococcus suis; adhesion and invasion mechanisms; molecular evolution of pathogenic streptococci; novel antimicrobials; vaccine development. This volume is essential reading for everyone working with streptococci from the PhD student to the experienced scientist, in academia, the pharmaceutical or biotechnology industries and for those working in clinical environments.